Python crash course : a hands-on, project-based introduction to programming - Matthes, Eric, 1972- (No Starch Press, 2023)
Python crash course' is the world's best-selling guide to the Python programming language. This fast-paced, thorough introduction will have you writing programs, solving problems, and developing functioning applications in no time. You'll start by learning basic programming concepts, such as variables, lists, classes, and loops, and practice writing clean code with exercises for each topic. You'll also learn how to make your programs interactive and test your code safely before adding it to a project. You'll put your new knowledge into practice by creating a 'Space invaders'-inspired arcade game, building a set of data visualizations with Python's handy libraries, and deploying a simple application online. As you work through the book, you'll learn how to: use powerful Python libraries and tools, including pytest, Pygame, Matplotlib, Plotly, and Django; make increasingly complex 2D games that respond to keypresses and mouse clicks; generate interactive data visualizations using a variety of datasets; build apps that allow users to create accounts and manage their own data, and deploy your apps online; troubleshoot coding errors and solve common programming problems. New to this edition: This third edition is completely revised to reflect the latest in Python code. New and updated coverage includes VS Code for text editing, the pathlib module for file handling, pytest for testing your code, as well as the latest features of Matplotlib, Plotly, and Django. If you've been thinking about digging into programming, 'Python crash course' will provide you with the skills to write real programs fast. Why wait any longer? Start your engines and code!